A new species of Lissoporcellana (Crustacea: Decapoda: Anomura: Porcellanidae) from Okinawa, southwestern Japan - Osawa, Masayuki; Fujita, Yoshihisa (Zootaxa, 2005)
Lissoporcellana flagellicola, a new porcellanid crab associated with an unidentified species of unbranched sea whip (Ellisellidae), is described from Okinawa-jima Island, the Ryukyu Islands, southwestern Japan. The new species appears close to L. quadrilobata (Miers) but differs by the less elongate carapace and the shape of the lateral lobes of the rostrum and terminal claws of the ambulatory dactyli.